2022
DOI: 10.1177/01430343221128825
|View full text |Cite
|
Sign up to set email alerts
|

Social-emotional classroom climate and academic achievement for Chinese elementary students: The roles of convergent and divergent thinking

Abstract: This study aims to explore the effects of the social-emotional classroom climate on academic achievement in mathematics and literature for elementary students in grades 3 through 6. The research specifically focuses on the indirect role of creative thinking (convergent and divergent thinking). Structural equation modeling techniques were used to examine data collected from 1365 Chinese elementary students. The results indicate that in mathematics and literature classrooms, (1) the social-emotional climate had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 96 publications
(107 reference statements)
0
0
0
Order By: Relevance
“…"In addition,(Javadi & Tahamsbi, 2019) suggests that learners could be engaged in activities related to learners" lives and experiences that involve excitement and emotions. Cheng et al (2022) conducted a study on the effects of the social-emotional classroom climate on academic achievement for elementary students. The results indicated that the social-emotional climate had a positive effect on school achievement, and divergent thinking plays an indirect role between social-emotional climate and academic achievement.…”
Section: Discussionmentioning
confidence: 99%
“…"In addition,(Javadi & Tahamsbi, 2019) suggests that learners could be engaged in activities related to learners" lives and experiences that involve excitement and emotions. Cheng et al (2022) conducted a study on the effects of the social-emotional classroom climate on academic achievement for elementary students. The results indicated that the social-emotional climate had a positive effect on school achievement, and divergent thinking plays an indirect role between social-emotional climate and academic achievement.…”
Section: Discussionmentioning
confidence: 99%